2018
DOI: 10.1007/s11103-018-0711-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of physiological and miRNA responses to Pi deficiency in alfalfa (Medicago sativa L.)

Abstract: The induction of miR399 and miR398 and the inhibition of miR156, miR159, miR160, miR171, miR2111, and miR2643 were observed under Pi deficiency in alfalfa. The miRNA-mediated genes involved in basic metabolic process, root and shoot development, stress response and Pi uptake. Inorganic phosphate (Pi) deficiency is known to be a limiting factor in plant development and growth. However, the underlying miRNAs associated with the Pi deficiency-responsive mechanism in alfalfa are unclear. To elucidate the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 78 publications
2
28
0
Order By: Relevance
“…In the third year of the study, the hay yield of P2 and P3 decreased approximately three times compared to the control under phosphate deficiency stress. Studies have shown that phosphate deficiency results in decreases in photosynthesis, reduced shoot, leaf, and biomass (Li et al, 2018) which is consistent with the results of this study. Moreover, significant decreases were observed in third year compared to the previous years in P2, and P3 in hay yield.…”
Section: Yield and Quality Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…In the third year of the study, the hay yield of P2 and P3 decreased approximately three times compared to the control under phosphate deficiency stress. Studies have shown that phosphate deficiency results in decreases in photosynthesis, reduced shoot, leaf, and biomass (Li et al, 2018) which is consistent with the results of this study. Moreover, significant decreases were observed in third year compared to the previous years in P2, and P3 in hay yield.…”
Section: Yield and Quality Parameterssupporting
confidence: 93%
“…miRs are known as regulators of many processes in plants against stress factors. Recent studies show that miRs can be involved with phosphate deficiency in several plant species (Zeng et al, 2016;Li et al, 2018;Ning et al, 2019). miR408 is one of the highly conserved miRNA family member in several plant species (Hajyzadeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By acting as miRNA sponges and competing for endogenous mRNAs, circRNAs play crucial roles in regulating functional gene expression and transcription [46]. Many miRNAs have been reported to participate in the response to P deficiency in various plant species by regulating the expression of target genes, including miR399 [47][48][49][50], miR319 [51], miR156 [52], and miR159 [53]. For example, a recent study in maize revealed that the PILNCR1-miR399 regulatory module is important for LP tolerance [47].…”
Section: Putative Functions Of Circrna-mediated Mirna Networkmentioning
confidence: 99%
“…Muhammad Arshad et al found that miR156 improved the drought resistance of alfalfa by acting on WD40-2 [31]. In addition, salinity-regulated [32], fall dormancy-related [33], freezing stress-related [34], and Pi deficiency-related [35] miRNAs have been identified in Medicago sativa. The above results suggest that miRNA plays a key role in the metabolism of alfalfa.…”
Section: Introductionmentioning
confidence: 99%